Testing the concurrent validity and reliability of a lipowise digital skinfold caliper to assess muscle mass in healthy young adults - Leão, César (2023)
The aim of this study was to assess the validity and reliability of a novel tool to assess skinfolds and to compare the muscle mass measured through dual-x-ray-absorptiometry (DXA) and estimated using the Lee equation from the values of the skinfolds and girths in a healthy young adult population. Methods: The present study followed a cross-sectional design, including 38 participants, with 27 males (22.04 ± 5.20 years) and 11 females (21.55 ± 2.39 years). The measurement protocol included a DXA evaluation, basic measurements of body mass and stature, eight skinfolds with two skinfold calipers of different brands (Harpenden and Lipowise), and three girths. The order in which the skinfold calipers were used was randomized. The muscle mass was then calculated using the formula established by Lee et al. Results: No significant differences were found between the two skinfold calipers considering all the outcomes (p > 0.05). The correlation coefficients were between 0.724 and 0.991, which suggest very-large to nearly perfect correlations. The correlations performed revealed that muscle mass estimated from DXA is nearly perfectly correlated with both muscle mass estimated from the data obtained with the Harpenden skinfold caliper (r = 0.955) and muscle mass estimated from the data obtained with the Lipowise skinfold caliper (r = 0.954). From the results, we conclude that Lipowise caliper is an accurate skinfold caliper and it can be an alternative tool for the technician that need to assess body fat or muscle mass in precise, valid and time efficient evaluation. It should be noted that the caution to use skinfold calipers interchangeable with each other when evaluating skinfolds remains a necessity and is advisable to perform the measurements with the same brand and model of skinfold caliper when the purpose is to perform follow-up assessments.